THE HYDROCHEMISTRY OF BAYELVA, A HIGH ARCTIC PROGLACIAL STREAM IN SVALBARD - Hodson A.; Tranter M.; Gurnell A.; Clark M.; Hagen J.O. (My University, 2002)
Major ion, silica and pH data from a high Arctic proglacial stream network are examined. Factor analysis shows that the major controls upon hydrochemistry in the basin include snowpack solute elution, rapid alteration of minerals via surface reactions and slow, incongruent silicate dissolution. The importance of chemical weathering is found to increase downstream at the expense of solute acquisition from the transient snowpack. Data from a series of snow pits show that snowpack solute elution is characterised by the preferential elution of SO42-. Evidence for the preferential elution of NO3- is equivocal. However, NO3- levels in proglacial runoff may be enhanced by the leaching of cryotic soils later in the ablation season.Chemical weathering is dominated by calcite dissolution at high elevations and a combination of calcite and dolomite dissolution in the downstream proglacial environment. Silicate weathering at high elevations is characterised by the enrichment of K+ relative to Si. Concentrated active layer soil waters show less enrichment of K+ and constitute a potentially important source of dissolved silica to the river system. Na+ is also produced by silicate weathering, but its mobility is believed to be largely governed by ion exchange with Ca2+ early in the ablation season.All chemical weathering environments are characterised by high p(CO2) due to either respiration within the soil or, at higher elevations within the catchment, H+ provision from acid aerosol and sulphide oxidation. However, rates of sulphide oxidation are limited because the cold-based thermal regime of the glaciers effectively prevents access of meltwaters to freshly comminuted sub-glacial sulphide minerals. The restricted sub-glacial weathering therefore means that ice marginal and proglacial environments are the most important zones of solute acquisition by meltwaters, causing significant enrichment of major ions, silica and dissolved CO2 within only a short distance of the contemporary ice margin.
Keywords: MELTWATER CHEMISTRY; CHEMICAL WEATHERING; SNOWPACK ELUTION; GLACIER HYDROLOGY; SVALBARD